Anti-bullying education at SDN 1 Sarajaya - Mahmudah; Muftikh, Afisa (Prosiding Seminar Nasional Pengabdian Masyarakat, 2024)
Bullying in schools is a problem that adversely affects the development of children and adolescents. These acts of bullying and bullying can cause trauma, anxiety, and even lead to depression and suicide. Therefore, it is important for all of us to unite and take action to stop bullying in schools. This community service aims to educate students in elementary schools on how to fight bullying. Through a socialisation approach, this service was carried out at SDN 1 Sarajaya. This activity involved children of SDN 1 Sarajaya grades 5 and 6. The results of the activity showed that students understood the education about bullying.